Nemu Gelang Wewengkon Desa lan Karang Paumahan of Bayung Gede as an Ecology-Based Local Wisdom - Mitha Mahastuti; Arya Wijaatmaja (Architectural Research Journal, 2024)
Bali has unique methods to preserve environment sustainability, for example: folklore, legend, tale, custom and concept that contain prohibition to do particular activities that could damage the environment. One of the ancient villages (Bali Aga) that has ecology friendly concept is Bayung Gede. This article tries to find how an ecology-based local wisdom evocation can sustain the environment in a growing rural area, especially in Bayung Gede. This article uses a qualitative method through observation and interview. Nemu Gelang refers to the layered green open space arrangement, which has architecture-profane and sacred functionality, on almost entire direction forms a series of layered “green barrier” which is called Nemu Gelang. The existence of these layered open spaces, in the traditional settlements known as "Nemu Gelang Desa" (the center of desa adat/indigenous village where Paumahan/settlements and Pura Kahyangan Tiga/3 village’s cardinal temples are located), while in the realm of the indigenous village area is called “Nemu Gelang Wewengkon Desa Adat”. Beyond the architectural functions, of the existence of these green open spaces remain sustainable for the future because: (i) Some are sacred (on all Setra/Graves and the Mertiwi temples) and (ii) all trees should not be hewn down and protected by Awig-Awig (village’s custom) certain with sanctions. The indigenous villagers of Bayung Gede strive to establish a harmony relationship with these green outdoor/spaces by obeying prohibition and Awig-Awig, and the final hope is that nature will provide protection and welfare for them. Although there are progress and development that changes the village physically, the society of Bayung Gede can sustain their environment through local wisdom evocation.